Detection of Schmallenberg virus antibody in equine population of Kurdistan province, west of Iran - Mahdavi, S; Salehzadeh, M; Montazeri, M (Journal of the Hellenic Veterinary Medical Society, 2023)
Schmallenberg virus (SBV) is a newly emerging virus in Simbu group. It is an arbovirus (virus transmitted by arthropods) that causes various complications in the fetus after infecting pregnant animals. The clinical signs of infection to this virus are fever, loss of appetite, reduced milk yield and in some cases, diarrhea and in pregnant animals, congenital malformations in calves, lambs, and kid goats. The aim of current study was to detect of Schmallenberg virus antibody in equine population of Kurdistan province, west of Iran. In this cross sectional study, blood samples from 184 horse in different rural areas of Kurdistan province (located in west of Iran) were analyzed using an indirect ELISA test. Risk factors of each sample such as sex, age, breed, history of abortion and the geographic location were taken into consideration. From a total of 184 serum samples that analyzed for the presence of antibody against SBV, 14.68% (n=27) of total samples was positive for SBV antibody, and 2.17% (n=4) was doubtful, and 83.15% (n=153) was negative. Except for the geographical area, there was no statistically significant difference between risk factors (p>0.05). The positive results of the samples tested in this study may show the high population and activity of Culicoides biting midges, their proper living conditions and illegal entry of infected livestock from other regions, especially from neighboring countries.